2010
DOI: 10.1007/s11432-010-4028-3
|View full text |Cite
|
Sign up to set email alerts
|

Key parameter estimation for radar rotating object imaging with multi-aspect observations

Abstract: Rotating object model is commonly used for imaging analysis in high resolution radars such as the inverse synthetic aperture radar (ISAR). For a rotating object, it is known that multi-aspect observations can improve cross-range resolution with the known imaging geometry. For the non-cooperative rotating object with unknown imaging geometry, this paper proposes an integrated scheme to estimate the key parameters, e.g., the rotating velocity and the aspect angle difference between every two observations. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Also, if target only rotated around y-axis with certain rotation speed yT ω and rotation acceleration ayT ω , then its time-varied location of above scattering center will be represented as (18) and its time-varied slant range can be rewritten as (19) From (19), it shown that the parameters yT ω and ayT ω will make main contribution for scattering center discrimination along z-axis, because they are closely related with scattering center's z-value. Furthermore, if target only rotated around zaxis with certain rotation speed zT ω and rotation acceleration azT ω , then its time varied location will be represented as (20) and its time-varied slant range can be rewritten as…”
Section: A Reduce Rotation Parameters For 3ds-rftmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, if target only rotated around y-axis with certain rotation speed yT ω and rotation acceleration ayT ω , then its time-varied location of above scattering center will be represented as (18) and its time-varied slant range can be rewritten as (19) From (19), it shown that the parameters yT ω and ayT ω will make main contribution for scattering center discrimination along z-axis, because they are closely related with scattering center's z-value. Furthermore, if target only rotated around zaxis with certain rotation speed zT ω and rotation acceleration azT ω , then its time varied location will be represented as (20) and its time-varied slant range can be rewritten as…”
Section: A Reduce Rotation Parameters For 3ds-rftmentioning
confidence: 99%
“…Recently, we proposed the Radon-Fourier transform (RFT) method [21~28] to realize the long-time coherent integration for a moving target with effective across range unit (ARU) compensation. Different from the existing Radon or Fourier transform [20,21], RFT can jointly compensate the envelope shifts and the phase modulations for moving targets of coherent radar. It is also shown that RFT is a generalized Doppler filter bank processing [21].…”
Section: Introductionmentioning
confidence: 99%
“…Bi-/multistatic radar has many advantages over monostatic radar: separated transmitter and receiver configurations offer the ability to detect stealthy targets and offer immunity to jamming; multistatic radar achieves spatially diverse geometries to observe threats and countermeasures from multiple viewing angles and provide highdetection performance. So Bi-/multistatic radar regains much more concern [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, wide aspect observations can be obtained by performing long-time observation with a monostatic ISAR or by acquiring multiaspect observations with multiple radar receiver configurations. 4 In other words, multiaspect observations can be utilized to form a higher-resolution two-dimensional (2-D) ISAR image as well as perform three-dimensional (3-D) reconstruction of a target. Reference 4 studies the parameter estimation of ISAR imaging with multiaspect observations, which further extends the application of multiaspect observations.…”
Section: Introductionmentioning
confidence: 99%